Evolution and current development of Transversal Themes: possibilities and limits (Foro de Educacion, 2024)
The aim of this study was to determine the characteristics of the evolution and current development of transversal themes in education, considering them basically as important social cuestions with great influence in the overall education of the student. Specifically it seeks to clarify the level of preparation and dedication of teachers and schools to teach them. To do this, legislation used in our country (organics laws and decrees curriculum) were analyzed and also the contribution of outstanding educators, institutions and researchers. We analyzed the characteristics of transversal themes in the educational project and the teaching program, its development in the clasroom and its projection out of it through the help of family and community. Conclusions about their current status (possibilities and limitations) are derived and future proposals are made on the improvement of initial and ongoing training of teachers, to increase their collegiate or cooperative work of planning, intervention and evaluation, increased media and counseling in use, the need for increased communication and collaboration with families and other community institutions.